Integrated fast optical modulators - Abdelatty, Mohamed Youssef (AUC Knowledge Fountain, 2019)
Over the past two decades, the demand for network interconnects, for both communication systems and intra/on-chip data links, increased in terms of capacities and bandwidth. To transmit digital signal over an optical traveling wave, the optical wave should be modulated using the digital electronic signal. An electro-optical modulator is responsible for switching the optical wave to pass or block it depending on the information digital signal. Such modulators are the key components in any optical communication system, since they convert the digital electronic signals to optical signals to travel over the optical fibers for long distances with minor losses. On chip level, copper interconnects are the bottleneck for the next generation technology because of their losses, dispersion, and speed. This has paved the way for replacing them with optical interconnects. Electro-optical modulators are the workhorses of such interconnects. To achieve the goal of replacing electrical interconnects with optical ones, a high level of integration should be accomplished. This can be only achieved by combining both optical and electrical components on the same substrate. Thus, silicon photonics is being a prominent candidate for this technology because of its low cost, and CMOS compatibility. Silicon as active material for optical modulation has a lot of limitations such as weak electro-optic effects and slow response of plasma dispersion effect. This raised the necessity for studying other novel alternative materials such as organic polymers, indium-tin-oxide (ITO), and vanadium dioxide. In this dissertation, novel electro-optical modulators, based on different active materials and different structures, are proposed. The main concern in these designs is the compatibility with the wide spread silicon CMOS technology. These modulators rely on the plasmonic theory to confine light beyond the diffraction limit. We introduce four high performance electro-optical modulators that operates under the telecommunication wavelength (1550 nm). An organic hybrid-plasmonic optical directional coupler is designed and studied. The power-splitting mechanism based on the change of the polymer electro-optical characteristics upon applying an external electric field. A finite element method with a perfect matching layer used to simulate this design. An extinction ratio of 14.34 dB is achieved for 39 Î¼m modulation length. Two hybrid silicon electro-optical modulators are introduced and analyzed. The active material for these designs is Indium-Tin-Oxide. The first is based on tri-coupled waveguides with electrical tuning mechanism that is designed to change both the coupling conditions and introduces additional intrinsic losses. Based on this design, extinction ratio of 6.14dB and insertion losses of 0.06 dB are realized at 21 Âµm modulator length; as well as, extinction ratio of 11.43 dB and insertion losses of 1.65 dB are realized at 34 Âµm modulator length. The second device is an electro-absorption modulator, based on dielectric slot waveguide with an ITO plasmonic modulation section. An extinction ratio of 15.49 dB and an insertion loss of 1.01 dB can be achieved for 10 Î¼m long modulation section. Modal and finite difference time domain analysis were performed to verify and simulate both designs. Last but not least, an optical switch based on a hybrid plasmonic-vanadium dioxide waveguide is presented. The power-attenuating mechanism takes the advantage of the phase change properties of vanadium dioxide that exhibits a change in the real and complex refractive indices upon switching from the dielectric phase to the metallic phase. An extinction ratio per unit length of 4.32 dB/Î¼m and insertion loss per unit length of 0.88 dB/Î¼m are realized. Also, Modal and finite difference time domain analysis are taken up to study and optimize this design. The proposed silicon electro-optical modulators can potentially play a key role in the next generation of the on-chip electronic-photonic integrated circuits.